2007
DOI: 10.1161/circulationaha.106.646661
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Gestational Age and Intrauterine Growth With Systolic Blood Pressure in a Family-Based Study of 386 485 Men in 331 089 Families

Abstract: Background-We conducted a family-based study to explore mechanisms underlying the associations of birth weight and gestational age with systolic blood pressure measured at 17 to 19 years of age. Methods and Results-A record linkage study of 386 485 singleton-born men from 331 089 families was undertaken. Birth weight was inversely associated with systolic blood pressure within siblings, with a mean difference (adjusted for age at examination, examination center, and year of examination) within siblings per 1-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 43 publications
(64 reference statements)
7
30
2
1
Order By: Relevance
“…This study reports an association between reduced gestation length and elevated 24-h systolic blood pressure in children, which supports several recent studies linking reduced gestational age to elevated blood pressure in adults [13][14][15][16][17][18][19] and children. [20][21][22] Furthermore, evidence is presented linking reduced gestation length with elevated pulse pressure in children, suggesting that early arterial stiffness may be involved in the causal pathway culminating in hypertension in adulthood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study reports an association between reduced gestation length and elevated 24-h systolic blood pressure in children, which supports several recent studies linking reduced gestational age to elevated blood pressure in adults [13][14][15][16][17][18][19] and children. [20][21][22] Furthermore, evidence is presented linking reduced gestation length with elevated pulse pressure in children, suggesting that early arterial stiffness may be involved in the causal pathway culminating in hypertension in adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies support this observation, linking earlier gestation and/or preterm birth with higher blood pressure in adults. [14][15][16][17][18] In a large family-based study of gestational age, intrauterine growth and blood pressure, Lawlor et al 19 provide evidence for an inverse association of gestational age with systolic blood pressure at age 17-19 years in both siblings and nonsiblings. Gestation length has also been linked to raised blood pressure in children.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational age, included because recent evidence suggests that this may be associated with cardiovascular disease risk factors, [18][19][20] was recorded as days since the start of last menstrual period at birth and converted into weeks. Height at age 7y was measured during medical examinations.…”
Section: Methodsmentioning
confidence: 99%
“…The link between preterm birth and hypertension risk (independent of birth weight) has been clearly demonstrated in a number of epidemiological studies. A significant inverse correlation between systolic blood pressure and gestational age at birth has been consistently observed from childhood to adulthood in preterm-born individuals [8][9][10][11][12][13][14][15][16][17][18][19][20][21] ; in particular, a recent meta-analysis demonstrated that systolic blood pressure in preterm-born children and young adults was an average of 2.5 mm Hg (95% confidence interval, 2.6-5.0 mm Hg) higher than those born at term. 21 We have also recently shown in a population-based study in Quebec, Canada, that women born preterm, particularly if birth occurred <32 weeks gestation, had an increased risk (independent of birth weight) of pregnancy complications (including gestational diabetes mellitus, gestational hypertension, and preeclampsia), as well as chronic hypertension compared with women born at term.…”
Section: Evidence From Epidemiological Studies: Preterm Birth and An mentioning
confidence: 97%